Penerapan Aplikasi Quizziz sebagai Kuis Interaktif pada Materi Teks Eksplanasi di SMPN 2 Semarang - Hesti Ambarwati; Asep Purwo Yudi Utomo; Tri Wahyuni; Indah Fitrianingrum; Didi Pramono; Umi Salamah; Tegar Arenanda Misbachar (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
Education in Indonesia is currently undergoing many changes. The education system, curriculum, learning tools, learning media, and resources have also undergone major improvements, especially after the Covid-19 pandemic. The learning process can not only be carried out face-to-face, but can also be done boldly. The application of learning media is designed to support students' attention, affective, cognitive, and compensatory. The Quizziz application can be a means of conducting formative assessments, because teachers can measure students' understanding by taking quizzes at the end of learning. The method used in this study is descriptive qualitative with subjects of class 8E students of SMPN 2 Semarang. The data collection techniques used are observation and documentation. The data analysis techniques used by researchers include three stages, namely data reduction, data presentation, and data conclusions. The results of this study show that the assessment format for class 8E students is on average above the KKM. The recapitulation results also show that the level of effectiveness of the questions used is by using multiple choice because in multiple choice questions students tend to get the best results, while in fill-in questions many students get less satisfactory results. The fill-in question model in the Quizziz application has several weaknesses, including if the teacher writes the answer key, the capitalization and punctuation must be correct. There is no tolerance for answers for students. Therefore, another option for teachers is to correct them manually. Another weakness in the Quizziz application with the multiple choice question model is that teachers cannot measure students' understanding in depth. Students tend to express their memory in answering.